CircCDYL Acts as a Tumor Suppressor in Wilms’ Tumor by Targeting miR-145-5p - Zhou, Rui; Jia, Wei; Gao, Xiaofeng; Deng, Fuming; Fu, Kai; Zhao, Tianxin; Li, Zhongmin; Fu, Wen; Liu, Guochang (Frontiers in Cell and Developmental Biology, 2021)
Circular RNAs have been reported to exert evident functions in many human carcinomas. However, the possible mechanisms concerning the circRNA in various tumors are still elusive. In this research, we analyzed the expression profile and biological functions of circular RNA CDYL (circCDYL, circBase ID: hsa_circ_0008285) in Wilms’ tumor. Here, miRNA and gene expression were examined by real-time PCR in Wilms’ tumor tissues and cell lines. The functions of circCDYL and its potential targets to influence cell proliferation, migration and invasion in Wilms’ tumor cells were determined by biological functional experiments in vitro and in vivo. We predicted and analyzed potential miRNA targets through online bioinformatic tools. To validate the interactions between circCDYL and its targets, we performed RNA fluorescent in situ hybridization, biotin-coupled miRNA capture assay and biotin-coupled probe pull-down assay. Tight junction protein l, TJP1 was proved to be the target gene of the predicted miRNA by dual-luciferase reporter assay. The expression level of TJP1 in Wilms’ tumor cells was identified via western blot. We showed that circCDYL was downregulated in WT tissue compared with adjacent non-tumor tissue. Upregulation of circCDYL could reduce cell proliferation, migration and invasion. Mechanically, circCDYL, functioning as a miRNA sponge, decreased the expression level of miR-145-5p and TJP1 3′UTR was validated as the target of miR-145-5p, facilitating the circCDYL/miR-145-5p/TJP1 axis. In conclusion, our study suggested circCDYL as a novel biomarker and therapeutic target for WT treatment.